Spectroscopic and physical–chemical characterization of ambazone–glutamate salt. Issue 2 (2011) - Mureşan-Pop, Marieta; Kacsó, Irina; Filip, Xenia; Vanea, Emilia; Borodi, G.; Leopold, N.; Bratu, I.; Simon, S.
Abstract : Ambazone monohydrate C8 H11 N7 S · H2 O (AMB), a well-known antimicrobial compound, was used together with Glutamic Acid C5 H9 NO4 (Glu) to obtain a new solid form using the solvent-drop grinding procedure. The screening of the new solid form was best achieved by the combined use of X-ray Powder Diffraction (XRPD) and several spectroscopic techniques (Fourier Transformed Infrared Spectroscopy (FTIR), X-ray Photoelectron Spectroscopy (XPS), Raman and 13 C-NMR spectroscopy) together with Differential Scanning Calorimetry (DSC), Differential thermal analysis and thermogravimetry (DTA–TGA). The combination of the mentioned analytical techniques allows the compound to be assigned to an ambazone–glutamate salt which crystallizes in monoclinic system having the following lattice parameters: a =9.8352, b =4.7014, c =40.0987 Å and β=94.505 ° . DSC, TGA data and the before mentioned spectroscopic techniques support the ambazone–glutamate salt formation.